Transient analysis and process optimization of the spatial atomic layer deposition using the dynamic mesh method. (18th May 2020) - Cong, Wentao; Li, Zoushuang; Cao, Kun; Feng, Guang; Chen, Rong
Highlights: A quantitative mathematical model adopting the dynamic mesh method is established to obtain a complete ALD cycle. The viscous dragging effect caused by the relative movement of the substrate is investigated through the dynamic model. Using the dynamic model, the spatial ALD process optimization and system design have been carried out. Abstract: Spatial atomic layer deposition (ALD) is acknowledged as a high-throughput thin film preparation technique. Since the films are obtained at a high relative velocity of the substrate, the dynamic flow field distribution is more intricate compared to the traditional ALD. In this paper, by adopting the dynamic mesh method, a mathematical model combing fluid dynamics with chemical kinetics is established. Quantitative analysis is carried out to evaluate how different parameters influence precursor intermixing through this dynamic model. The viscous dragging effect caused by the relative movement of the substrate is also investigated. The good agreement between the mathematical results and the experimental data demonstrates the effectiveness of the dynamic model. To obtain a uniform thin film with a relatively high deposition rate and precursor usage, the motion speed of the substrate is also optimized. This numerical model has momentous guidance to the further process optimization and the spatial ALD system design.